GAYA BELAJAR, MOTIVASI BERPRESTASI, LOCUS OF CONTROL DAN ACADEMIC SELF-CONCEPT MAHASISWA FIK UNCEN - miftah fariz putra (Journal of Sport Science and Education, 2017)
The aim of this research was to find out (1) profile of learning style, achievement motivation, locus of control, academic self-concept of the college student of FIK Uncen, (2) difference of learning style, achievement motivation, locus of control, academic self-concept of the college student of FIK Uncen to view gender.  The result of this research was (1) there was 7 (9,6%) college students that have visual learning style, 19 (26,0%) college students that have aural learning style, 16 (21,9%) college students that have read/write learning style, 31 (42,5%) college students that have kinesthetic learning style. There was no difference learning style to view gender, (2) the mean of achievement motivation of the effort dimension have more higly score (29) than both the choice dimension (21) and the persistence dimension (19). There was no difference achievement motivation to view gender, (3) there was 63 (86,3%) college students that have internal locus of control and 10 (13,7%) college students have external locus of control. There was no difference locus of control to view gender (4) there was 18 (24,7%) college students that have high academic self-concept, 55 (75,3%) college students that have medium academic self-concept, and 0 (0%) college students that have low academic self-concept. There was no difference academic self-concept to view gender. Key words: Gaya belajar, motivasi berprestasi, locus of control, academic self-concept